Landis Wine Labels (two) - Pickford, Rollin:::::::::
Labels designed by Rollin Pickford for the Landis winery. Only Cream Sherry and Ruby Cabernet were produced before the winery went out of business. The Landis family were very close friends of the Pickford family.